Exploitation of dark fermented effluent of cheese whey by co-culture of Rhodobacter sphaeroides and Bacillus firmus for photo-hydrogen production - Pandey, A.; Pandey, A. (Cellular and Molecular Biology, 2017)
In this study photo-hydrogen production from cheese whey dark fermentation (DF) effluent by the co-culture of Rhodobacter sphaeroides –NMBL-01 and Bacillus firmus – NMBL-03 has been reported. The effect of pH, initial chemical oxygen demand (COD) and the concentration effect of FeSO4.7H2O on photo-hydrogen production have been investigated. The end products of dark fermentation effluent of cheese whey were mainly comprised of soluble organic acids, i.e. butyric acid and lactic acid. The batch process was carried out under light intensity of 2.5 kLux at 32 ± 2oC without any addition of extra carbon and nitrogen source. The single parameter optimization studies revealed optimum pH 6.5, initial COD 4.71 g/L and supplementation of Fe2+ concentration 100 mg/L. The maximum cumulative hydrogen production and yield were found to be 469 ± 45.8 ml H2/L and 146.56 ± 14.31 ml H2/g COD reduced (67.9% reduction in COD) respectively. The mutual interactions among the process parameters were also investigated by three factorial Box-Behnken design of response surface methodology. The optimized experimental values were found concurrent with the calculated values obtained from the theoretical model.